Accounting for the elemental. (March 2015) - Adey, Peter
This response outlines two particular tendencies evident within the generous series of contributions brought together in dialogue with my article. One of those is a concern for the political. How to push, sharpen, or, for some, retrieve the potential for critique from the line of argumentation around the elemental and the possibilities of affinitive listening that I try to develop in the article? Is it necessary to actually dispense with this particular way of addressing the elemental in order to do this? The second, which potentially negates the possibility of the latter, is not really whether but how we might think more elementally, not less. How can we devote more consideration to a different kind of politics and ethics? My response addresses these issues by exploring how critique and elemental approaches might not necessarily work against but with one another.